Systematic Review Human Resource Management: Innovation, Knowledge, Compensation, Performance and Employment Relations - Siagian, Mauli (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Previous research has dedicated significant attention to the analysis of Human Resource Management (HRM) issues, with a specific focus on employee performance. It has been widely acknowledged that employee performance is intricately linked to the HRM process itself. Notably, studies have demonstrated that ineffective planning to maximize employee competence has a detrimental impact on performance, consequently influencing individual outcomes within the organization. Building upon these insights, the present study delves further into the crucial role of the planning process within HRM. Specifically, the research investigates how a manager’s cognitive processes, including their knowledge and capacity to identify and establish connections among various performance-related factors, significantly contribute to the overall success and sustainability of a company or organization. By serving as the driving force behind the formulation and implementation of effective HRM strategies, the planning process emerges as a fundamental element in shaping organizational outcomes.This study highlights the critical role played by the planning process in HRM and its profound impact on employee performance and organizational outcomes.